ANALYSIS AND MONITORING OF RIVER WATER QUALITY IN TASIKMALAYA CITY - Nurcholis Salman (Department of Environmental Engineering - Universitas Pasundan - Indonesia, 2021)
The rivers passing through the City of Tasikmalaya include the Citanduy River, the Ciloseh River, the Ciwulan River and the Cibanjaran River. While the tributaries are the Cibanjaran River which include the Cihideung/ Dalem Suba River, the Cipedes River, the Ciromban River, the Cidukuh River, the Cicacaban River, the Cibadodon River, the Cikalang River, the Tonggong Londok River, the Cibeureum River and the Cimulu River. These rivers flow and empty into the Citanduy River. The aims and objectives of this study are environmental quality monitoring activities, especially the quality of river water in the Tasikmalaya City. To find out in more detail and carefully the level of pollution that occurs, this study aims to conduct water quality monitoring so that the resulting data can determine the source of pollutants that cause deterioration of river water quality. Monitoring was conducted during the rainy season and the dry season. Based on the monitoring, it appears that the river being monitored does not meet the quality standards as a class II water body with varying status ranging from lightly polluted to heavily polluted. Parameters that do not meet quality standards include TSS, BOD, COD, nitrite, Cr6+, Zn, free chlorine, Total Phosphate, oil and fat, E. Coli and Total Coliform.